2009
DOI: 10.1136/bmj.b4904
|View full text |Cite
|
Sign up to set email alerts
|

Health and disease in 85 year olds: baseline findings from the Newcastle 85+ cohort study

Abstract: Objectives The Newcastle 85+ Study aims to systematically study the clinical, biological, and psychosocial attributes of an unselected cohort of 85 year olds and to examine subsequent health trajectories as the cohort ages; health at baseline is reported. Design Cross sectional analysis of baseline data from a cohort study. Setting Newcastle upon Tyne and North Tyneside primary care trusts, United Kingdom. Participants 1042 people born in 1921 and registered with the participating general practices. Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
424
5
6

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(450 citation statements)
references
References 27 publications
15
424
5
6
Order By: Relevance
“…70 Moreover, management of these conditions, in particular self-management, is likely to be complicated by the presence of dementia. 21 VI is also prevalent in older people 71 and may exacerbate confusion. 72 In addition, the ability to cope with VI is reduced if a person also has dementia.…”
Section: Phasementioning
confidence: 99%
“…70 Moreover, management of these conditions, in particular self-management, is likely to be complicated by the presence of dementia. 21 VI is also prevalent in older people 71 and may exacerbate confusion. 72 In addition, the ability to cope with VI is reduced if a person also has dementia.…”
Section: Phasementioning
confidence: 99%
“…En tal sentido, al enfocarse en la prueba TUG se observa una tendencia de mejor rendimiento de los hombres respecto a las mujeres entre los 60 y 80 años. Sin embargo, en los octogenarios esto disminuye, lo cual podría obedecer a dos factores: las características funcionales de quienes han logrado un envejecimiento exitoso [28][29][30] y haber preservado condiciones similares al efecto deletéreo acumulado por la edad 18 .…”
Section: Discussionunclassified
“…The recruited cohort was sociodemographically representative of England and Wales and included institutionalised and cognitively impaired very old adults (16) . The study received ethical approval from the Newcastle and North Tyneside 1 Research Ethics Committee (06/Q0905/2).…”
Section: Uk and New Zealand Cohort Studies Of Health And Ageing In Admentioning
confidence: 99%
“…Specifically, diet quality has been linked to socioeconomic status defined either by education, social class (occupation) and income in general and older adults populations (aged 60 and over) (56)(57)(58) , but to which extent and which dimension socioeconomic status plays a role in diet characteristics in very late life is not known. Utilising dietary data collected by 24-h multiple-pass dietary recalls from participants in the Newcastle 85+ study (16,17,34) and two-step clustering, we identified three distinct DP, which differed with respect to the key sociodemographic, lifestyle, health and functioning measures (59) . 'High Red Meat' DP had the highest proportion of participants (and the highest mean intake (g/d)) consuming red and processed meats/meat dishes, potato/potato dishes, gravy, legumes (including baked beans) and unsaturated fats spreads, but the lowest consumption of butter.…”
Section: Dietary Patterns and Health In The Very Oldmentioning
confidence: 99%